Widespread introgression in deep-sea hydrothermal vent mussels. Issue 1 (December 2017) - Breusing, Corinna; Vrijenhoek, Robert; Reusch, Thorsten
Abstract Background The analysis of hybrid zones is crucial for gaining a mechanistic understanding of the process of speciation and the maintenance of species boundaries. Hybrid zones have been studied intensively in terrestrial and shallow-water ecosystems, but very little is known about their occurrence in deep-sea environments. Here we used diagnostic, single nucleotide polymorphisms in combination with one mitochondrial gene to re-examine prior hypotheses about a contact zone involving deep-sea hydrothermal vent mussels, Bathymodiolus azoricus andB. puteoserpentis, living along the Mid-Atlantic Ridge. Results Admixture was found to be asymmetric with respect to the parental species, while introgression was more widespread geographically than previously recognized. Admixed individuals with a majority of alleles from one of the parental species were most frequent in habitats corresponding to that species. Mussels found at a geographically intermediate vent field constituted a genetically mixed population that showed no evidence for hybrid incompatibilities, a finding that does not support a previously inferred tension zone model. Conclusions Our analyses indicate thatB. azoricus andB. puteoserpentis hybridize introgressively across a large geographic area without evidence for general hybrid incompatibilities. While these findings shed new light onto the genetic structure of this hybrid zone, many aspects about its nature still remain obscure. Our study sets a baseline for further research that should primarily focus on the acquisition of additional mussel samples and environmental data, a detailed exploration of vent areas and hidden populations as well as genomic analyses in both mussel hosts and their bacterial symbionts.